Work-related outcomes in individuals with and without lower limb osteoarthritis: an online survey - Yousef S. Alyousef; Venerina Johnston; Michelle D. Smith (BMC, 2023)
Abstract Objective While osteoarthritis (OA) affects people who are still participating in the workforce, there is limited data about the impact of OA on work. The aim of this study was to compare work participation in individuals with and without lower limb OA. Methods This cross-sectional study included workers with (n = 124) and without (n = 106) lower limb OA. Work participation was assessed as work status (full/part time work), work ability (Work Ability Index (WAI)), absenteeism and presenteeism (World Health Organization's Health and Work Performance Questionnaire (WHO-HPQ)), and perceived difficulties meeting work demands (Work Role Functioning Questionnaire (WRFQ)). The data were analyzed using an analysis of covariance with age, body mass index and physical job demands included as covariates. Results Work ability was poorer (p < 0.001) and loss of work performance (p < 0.001) was higher among workers with OA than healthy controls. There was no statistical difference in absenteeism or overall ability to meet work demands between participants with and without lower limb OA. However, workers with lower limb OA had more difficulty with work scheduling demands (p = 0.05) and physical demands (p = 0.003) than healthy workers. Conclusion Lower limb OA was associated with poorer work ability, loss of work performance and difficulty in meeting physical and work scheduling demands. Health professionals and employers should consider these challenges when managing individuals with lower limb OA and supporting them to remain in the workforce.